AL-ISLAM KEMUHAMMADIYAHAN: DASAR KEAGAMAAN GERAKAN MUHAMMADIYAH INDONESIA - Yuldafriyenti (LPPM STAI Muhammadiyah Probolinggo, 2024)
This research aims to determine whether al-Islam Kemuhamadiyah is the religious basis of the Indonesian Muhamadiyah Movement. We employ literature study as our research method. Religion plays a crucial role in the structure of human life, serving as the foundation for all aspects of global existence. KH Ahmad Dahlan founded Muhammadiyah Indonesia, a contemporary Islamic religious organization, on November 28, 1912. This movement preaches amar ma'ruf nahi munkar, or the defense of the Islamic religion, with the goal of forming a genuine Islamic society. Muhamadiyah is an Islamic religion based on the pure teachings of the Koran and hadith that aims to restore, improve, encourage, foster, and improve human life. Muhammadiyah is an Islamic reform movement in Indonesia that seeks to eradicate bit'ah, superstition, and kurafat from public culture. Muhammadiyah is committed to developing healthy and pure thoughts.Keywords: Religious; Muhammadiyah Movement; Movement Models